1988
DOI: 10.1007/bf02431534
|View full text |Cite
|
Sign up to set email alerts
|

Possible interactions between zolpidem, a new sleep inducer and chlorpromazine, a phenothiazine neuroleptic

Abstract: The combined use of a hypnotic and a neuroleptic is a rather frequent situation, encountered especially in the psychiatric sphere. We therefore tested zolpidem and chlorpromazine in six healthy subjects by using a double-blind latin square design. All of them received single doses of 20 mg zolpidem (ZOL), 50 mg chlorpromazine (CPZ) and the combination of ZOL + CPZ. The medication was given as a single dose in the morning and each treatment being separated by a 1-week interval. Zolpidem produced moderate to sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 7 publications
3
7
0
1
Order By: Relevance
“…For example, zolpidem is metabolized via CYP3A4, and acts as a mild mechanism-based inactivator of human CYP3A in vitro [29, 30]. In contrast, gabapentin is non-metabolized and is eliminated renally primarily as unchanged drug, showing plasma clearance that is proportional to creatinine clearance [6].…”
Section: Discussionmentioning
confidence: 99%
“…For example, zolpidem is metabolized via CYP3A4, and acts as a mild mechanism-based inactivator of human CYP3A in vitro [29, 30]. In contrast, gabapentin is non-metabolized and is eliminated renally primarily as unchanged drug, showing plasma clearance that is proportional to creatinine clearance [6].…”
Section: Discussionmentioning
confidence: 99%
“…The Stroop color-word test appears to be especially sensitive to drug effects,[89101112202122232425262728] as indicated by previous work and Zolpidem and caffeine may affect any of a number of cognitive skills used on such a complex task as the Stroop color-word test. Arnett et al .…”
Section: Discussionmentioning
confidence: 99%
“…[20] in which Zolpidem (20 mg) produced increase in RT latencies up to 3 hours after drug intake in Stroop test. The effect of benzodiazepines on Stroop interference demonstrated a variety of results.…”
Section: Discussionmentioning
confidence: 99%
“…Longer reaction times and/or reductions in the percentage of correct responses made in concert with increasing doses of zolpidem suggest that participants may have become increasingly inattentive to the stimuli being presented. Alternatively, these behavioral data may indicate that participants succumbed to the motor-impairing effects of zolpidem (Licata et al, 2009), particularly because manual dexterity has been shown to decline following a high dose of zolpidem (Desager et al, 1988). Additional evidence against attentional deficits underlying the decrease in BOLD signal was reported in conference proceedings indicating that although diverting attention away from a visual stimulus during passive viewing induces a widespread negative BOLD response in visual areas outside of V1, it has little effect on BOLD contrast within V1 (Zhang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%